(untitled) (Boston, 1997)
Contents: Present status of Larval rearing in the world; marine rotifers; other live food organisms; larval rearing
Keywords: Marine fishes,Shellfish,Live food,Cá biển; Feeding and feeds,Feeding and feeds,Nuôi và cho ăn